2018
DOI: 10.1111/gcb.14491
|View full text |Cite
|
Sign up to set email alerts
|

The response of stocks of C, N, and P to plant invasion in the coastal wetlands of China

Abstract: The increasing success of invasive plant species in wetland areas can threaten their capacity to store carbon, nitrogen, and phosphorus (C, N, and P). Here, we have investigated the relationships between the different stocks of soil organic carbon (SOC), and total C, N, and P pools in the plant–soil system from eight different wetland areas across the South‐East coast of China, where the invasive tallgrass Spartina alterniflora has replaced the native tall grasses Phragmites australis and the mangrove communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 75 publications
(101 reference statements)
1
56
0
1
Order By: Relevance
“…Grasses in the genus Spartina have been aggressive invaders of coastal habitats worldwide (Strong & Ayres, 2013). In these new habitats, S. alterniflora typically transforms intertidal mudflats into high‐intertidal salt marshes, with profound consequences for above‐ground plant communities (Biswas et al, 2018; Li et al, 2009), migratory shorebirds (Ma, Gan, Choi, & Li, 2014), macroinvertebrate communities (Neira, Levin, Grosholz, & Mendoza, 2007), hydrologic and edaphic parameters (Adams et al, 2012), and soil biochemistry (Wang et al, 2019). Our work has shown that the geographic structure of nematode communities is also affected (Zhang, Pennings, et al, 2019; this paper), emphasizing both the importance of examining the soil food web and the importance of taking a geographic approach to studying species invasions.…”
Section: Discussionmentioning
confidence: 99%
“…Grasses in the genus Spartina have been aggressive invaders of coastal habitats worldwide (Strong & Ayres, 2013). In these new habitats, S. alterniflora typically transforms intertidal mudflats into high‐intertidal salt marshes, with profound consequences for above‐ground plant communities (Biswas et al, 2018; Li et al, 2009), migratory shorebirds (Ma, Gan, Choi, & Li, 2014), macroinvertebrate communities (Neira, Levin, Grosholz, & Mendoza, 2007), hydrologic and edaphic parameters (Adams et al, 2012), and soil biochemistry (Wang et al, 2019). Our work has shown that the geographic structure of nematode communities is also affected (Zhang, Pennings, et al, 2019; this paper), emphasizing both the importance of examining the soil food web and the importance of taking a geographic approach to studying species invasions.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of invasive species on N and P cycles and stoichiometry on the plant–soil system may vary between nutrient‐rich and nutrient‐poor ecosystems (Gonzalez et al, ; Matzek, ; Sardans, Bartrons, et al, ). For example, successful invasive species have higher capacities to take up and efficiently use nutrients that are limited (Aragon, Sardans, & Penuelas, ; Sardans, Bartrons, et al, ; Ulm et al, ; Wang, Sardans, et al, ; Wang, Wang, et al, ), so the concentrations of N and P in photosynthetic tissues tend to be higher in invasive than native species. Total soil N concentrations and availabilities of N and P correlated with higher mineralization capacity are higher for invasive species, particularly in nutrient‐poor environments (Sardans, Bartrons, et al, ).…”
Section: Shifts In N:p Ratios Mediated By Anthropogenic Drivers Of Glmentioning
confidence: 99%
“…Since its initial appearance on the Chongming Dongtan salt marsh during the 1990s, S. alterniflora has gradually colonized the bare mudflats and invaded the habitat historically occupied by native P. australis and S. mariqueter communities (Li et al, ; Tang et al, ). The S. alterniflora was therefore identified as a coastal invasive plant by the State Environmental Protection Administration of China in 2003 (Li et al, ; Wang et al, ). The distribution area of S. alterniflora reached about 1,500 ha in the Chongming Dongtan salt marsh and more than 6,000 ha in the Yangtze River Estuary in 2012 (Ge et al, ).…”
Section: Methodsmentioning
confidence: 99%